Isolated FeN4 sites for efficient electrocatalytic CO2 reduction - Li, Xiaogang (2020)
The construction of isolated metal sites represents a promising approach for electrocatalyst design toward the efficient electrochemical conversion of carbon dioxide (CO2). Herein, Fe‐doped graphitic carbon nitride is rationally prepared by a simple adsorption method and is used as template to construct isolated FeN4 sites through a confined pyrolysis strategy, which avoids the agglomeration of metal atoms to particles during the synthesis process and thus provides abundant active sites for the CO2 reduction reaction. The isolated FeN4 sites lower the energy barrier for the key intermediate in the CO2 reduction process, leading to the enhanced selectivity for CO production with a faradaic efficiency of up to 93%.